Estimating matching games with transfers - Jeremy T. Fox (Quantitative Economics, 2018)
I explore the estimation of transferable utility matching games, encompassing many-to-many matching, marriage, and matching with trading networks (trades). Computational issues are paramount. I introduce a matching maximum score estimator that does not suffer from a computational curse of dimensionality in the number of agents in a matching market. I apply the estimator to data on the car parts supplied by automotive suppliers to estimate the valuations from different portfolios of parts to suppliers and automotive assemblers.
Keywords: C35; C57; C78; L14; L62; 330; Matching; trading networks; relationship formation; semiparametric estimation; maximum score